Empowering Women Through TAGABA (Emergency Response For Toddlers) As Health Community Empowerment For 'Aisyiyah Cadres In Kalibagor Banyumas - Kusuma, Inggar Ratna; Riani, Evicenna Naftuchah; Septianawati, Paramita (Edumedia Solution, 2025)
The infant mortality rate in Indonesia is still high, reaching 19.83% / 100,000 live births. Meanwhile, the child mortality rate in Indonesia due to accidents, poisoning and trauma is recorded at 7.3% / 100,000 live bitrh) and is one of the five highest causes of child mortality. Health Community Empowerment (HCE) is an effort to empower communities to improve health levels. HCE includes several elements of active community participation, health education, cross-sector collaboration, and access to health services. Through increased knowledge, awareness, attitudes and behaviors will increase to improve health, especially for toddlers.The objectives of this activity include helping to reduce morbidity in newborns, neonates and toddlers. Helping to reduce infant, neonatal and toddler mortality due to illness or injury. Increasing the knowledge and skills of 'aisyiyah cadres regarding emergency management of injuries and diseases. Increasing public knowledge to behave in a clean, healthy lifestyle and parenting patterns to improve health. The form of this activity is in the form of first aid training for toddlers who have accidents at home including choking, burning, poisoning, electric shock. This training was attended by 20 mothers who have toddlers in Kalibagor Village, Banyumas. The output of this activity is in the form of posters, HAKI, scientific journals, activity videos, and gradual improvement of partner skills.